2005
DOI: 10.1063/1.1879074
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of A- and B-site-doped BaTiO3(I):La- and Al-doped solid solutions

Abstract: Extremely small amounts of La and Al doping on the A and B site of BaTiO 3 , respectively, resulting in a solid solution of the type Ba 1-3x La 2x Ti 1-3x Al 4x O 3 have been investigated. The compositions have been prepared by the Pechini process. The x-ray diffraction ͑XRD͒ reveals the presence of tetragonal ͑P4/mmm͒ phase. The XRD data has been analyzed using FULLPROF, a Rietveld refinement package. The compositions have been characterized by dielectric spectroscopy between room temperature and 200°C. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…2 A large number of these exhibit a relaxortype behavior. The features of a relaxor behavior are diffused phase transition, deviation from Curie-Weiss ͑CW͒ law, spontaneous polarization over an extended temperature range, and frequency dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…2 A large number of these exhibit a relaxortype behavior. The features of a relaxor behavior are diffused phase transition, deviation from Curie-Weiss ͑CW͒ law, spontaneous polarization over an extended temperature range, and frequency dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…The real permittivity value for the BT1 ceramics is the lowest, but in the BT2 ceramics, that have the same Nb concentration but lower Mn contribution, the real permittivity value is higher. Therefore, Mn in this case, influenced the decrease of permittivity of the material, which was noticed by other authors [14]. Since the Mn incorporated in the oxygen octahedron of the BT is in more centered position than Ti 4 þ , it may modify considerably the ferroelectricity as well as permittivity of the material [22].…”
Section: Resultsmentioning
confidence: 68%
“…For the BT1 and BT2 ceramics, that possess the same concentration of Nb, all structural transitions are located at almost the same position (Table 1). On the other hand, for the BT3 ceramic which has higher concentration of Nb, the structural transition T C-T shifted to the lower temperatures, whereas other two transitions T T-O and T O-R have moved to higher temperatures indicating the so called "pinching effect" [14]. Literature data confirmed that addition of niobium as a dopant in the barium titanate lattice could cause a shift of the T C-T phase transition to lower temperatures [15,16].…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, comparing with the dielectric constant 36.8 of Ba 4 ZnTi 11 O 27 ceramics [6], the dielectric constant about 35.4-37.9 of BZT ? x wt% BaCu(B 2 O 5 ) ceramics sintered at 900°C didn't deteriorate because the BaTiO 3 phase with a very high dielectric constant appeared in these ceramics [12].…”
Section: Experiments Proceduresmentioning
confidence: 99%